(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Effects of supplemental dietary lysine and methionine in a Groundnut Cake (GNC) based diets on meat and bone characteristics of broiler chickens were investigated. In a completely randomized design, a total of 168 one - day – old Arbor acre broiler chicks were randomly allocated to seven dietary treatments each in triplicate of eight birds per replicate. The Seven starter and finishers’ diets were: GNC based diets without any amino acid (lysine or methionine) supplementation (T1); GNC diet + 0.2% lysine (T2); GNC diet + 0.4% lysine (T3); GNC diet + 0.2% methionine (T4); GNC diet + 0.4% methionine (T5); GNC diet + 0.2 lysine and 0.2% methionine (T6) and GNC diet + 0.4% lysine and 0.4% methionine (T7). Experimental diets and water were offered to birds ad libitum in an experiment lasting six-week. At day 42, two birds per replicate were slaughtered, meat and bone characteristics determined. There were significant variations (P<0.05) in the crude protein (%) and ether extract (%), pH1 and pH2 of meat. Thiobarbituric acid reactive substances composition of meat at days 0, 5, and 10 were similar (P<0.05) and were not affected by dietary amino acid supplementation. Tibiotarsal index (mg/mm) of bone (22.10, 27.25, 33.35, 31.40, 28.70, 31.45 and 29.75 for broilers on T1, T2, T3, T4, T5, T6 and T7, respectively) were increased significantly (P<0.05) by amino acid supplementation. Significantly differences (P<0.05) were observed in the calcium, phosphorus and potassium (%) contents of broilers’ bone across treatments. Supplemental lysine and both lysine and methionine improved meat quality and bone development of broiler chickens in this study.